Behavioral Counseling Training for Primary Care Providers: Immersive Virtual Simulation as a Training Tool - Gavarkovs, Adam G. (Frontiers in Public Health, 2019)
Behavioral counseling represents an efficacious approach for improving health behaviors on a population level, and the primary care setting is an appropriate context in which to implement this approach. However, evidence suggests that the utilization of behavioral counseling techniques in primary care, including those informed by motivational interviewing, is sub-optimal. Insufficient training has been cited as a barrier to utilizing counseling in the primary care setting. Recent work has evaluated the effectiveness of virtual simulations that can provide access to ‘virtual’ patients while retaining the scalability inherent to a digital medium. However, these educational interventions have been limited to simulations delivered through a two-dimensional screen. More immersive simulations delivered through a head mounted display can create a realistic practice environment that encompasses a learner’s entire field of view, which may confer additional benefits with respect to training outcomes. The purpose of this short article is to briefly review the relevant literature across disciplines to conceptualize the potential effectiveness of this technology as a training tool for behavioral counseling. Immersive virtual simulations are designed to induce a psychological phenomenon referred to as presence, whereby a learner perceives themselves as existing within the virtual environment. As such, immersive virtual simulations can provide opportunities for practice, coaching, and feedback in an environment that closely approximates the clinical setting in which counseling will be delivered. Through its effects on presence, this technology may be particularly useful for developing empathy, which is an important component of counseling. Recommendations for future research are also provided.